2007
DOI: 10.1534/genetics.106.069443
|View full text |Cite
|
Sign up to set email alerts
|

A Fitness Cost Associated With the Antibiotic Resistance Enzyme SME-1 β-Lactamase

Abstract: The bla TEM-1 b-lactamase gene has become widespread due to the selective pressure of b-lactam use and its stable maintenance on transferable DNA elements. In contrast, bla SME-1 is rarely isolated and is confined to the chromosome of carbapenem-resistant Serratia marcescens strains. Dissemination of bla SME-1 via transfer to a mobile DNA element could hinder the use of carbapenems. In this study, bla SME-1 was determined to impart a fitness cost upon Escherichia coli in multiple genetic contexts and assays. G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
48
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(52 citation statements)
references
References 63 publications
1
48
0
1
Order By: Relevance
“…Alternatively, Marciano et al suggested that the signal peptide of the class A carbapenemase SME-1 might be responsible for cell lysis and plasmid rearrangements in an E. coli strain, either by forming pores on the bacterial cell wall or by hijacking the protein synthesis machinery (33). Whether the signal peptide of VIM-2 is accountable for the deleterious effects observed in S. Typhimurium remains to be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, Marciano et al suggested that the signal peptide of the class A carbapenemase SME-1 might be responsible for cell lysis and plasmid rearrangements in an E. coli strain, either by forming pores on the bacterial cell wall or by hijacking the protein synthesis machinery (33). Whether the signal peptide of VIM-2 is accountable for the deleterious effects observed in S. Typhimurium remains to be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study by Call et al (6) showed that the bla CMY-2 region of pAR060302 is prone to stochastic excision and, in the absence of selection pressure, populations of E. coli harboring bla CMY-2 were outcompeted by bla CMY-2 -lacking plasmids over many generations. Other studies have shown a significant cost of carrying other variants of AmpC-like ␤-lactamase genes (18,26). It was hypothesized that this cost is a result of unregulated expression and that this cost of carriage results in reduced dissemination.…”
Section: Discussionmentioning
confidence: 99%
“…Genes whose presence significantly reduces cell fitness are rapidly lost in the absence of selection, whereas those that come at a low cost can stably persist in the cells, even when pathogens are not exposed to antibiotics (1,3,10,18,23,24,35,44). Therefore, knowing the fitness cost of a resistance mechanism is important for predicting the efficiency of its maintenance and the rate of expansion.…”
mentioning
confidence: 99%